High-Dose Neural Stem/Progenitor Cell Transplantation Increases Engraftment and Neuronal Distribution and Promotes Functional Recovery in Rats after Acutely Severe Spinal Cord Injury - Taoyang Yuan; Qian Liu; Jie Kang; Hua Gao; Songbai Gui (Hindawi Limited, 2019)
Severe spinal cord injury (SCI) leads to permanent, complete paraplegia and places considerable mental and economic burdens on patients, compared with mild to moderate SCI. However, the dose-related effects of the neural stem/precursor cell (NSPC) transplantation on the injury microenvironment, NSPC survival, axonal growth, neuronal distribution, the composition of neurons, oligodendrocytes, and astrocytes in the lesion area and functional recovery have not yet been quantitatively evaluated in the context of severe SCI. In our study, we acutely transplanted 2.5×104 or 1.5×105 NSPCs/μl into the site of transection SCI. We found that high-dose NSPC transplantation exerted immunomodulatory and neuroprotective effects in the acute phase of severe SCI. In addition, one week later, a remarkable positive relationship was observed between the transplantation dose and the number of surviving NSPCs in severe SCI. At 8 weeks postgrafting, subjects that received the higher cell dose exhibited abundant nerve regeneration, extensive neuronal distribution, increased proportions of neurons and oligodendrocytes, and nascent functional neural network formation in the lesion area. Notably, a significant functional recovery was also observed. Our data suggest that it is important to consider potential dose-related effects on donor cell survival, neuronal distribution, and locomotor recovery in the development of preclinical NSPC transplantation therapy for severe SCI.